Legalitas Penjual Bahan Bakar Minyak Eceran - Mahulette, Muhammad Syamsudin; Akyuwen, Rory Jeff; Kuahaty, Sarah Selfina (KANJOLI Business Law Review, 2023)
Due to the impact of the increase in fuel prices, many motor vehicle users buy more often from retailers because it is faster and there is no need to queue even though the prices tend to be more expensive. In Article 43 to Article 53 of Government Regulation Number 36 of 2004 concerning Downstream and Natural Gas Business Activities, it is clear that this Regulation only regulates business entities, this means that those who can carry out trading activities in fuel oil are business entities, but we have encountered many In reality, many retail fuel oil sellers are carried out by individuals who are not licensed business entities. The method used in this research is Normative Juridical and in this research it prioritizes primary legal materials, secondary legal materials and tertiary legal materials. And the problem approach used is a statutory approach and a conceptual approach, then the collection of legal materials used in this research uses literature study and analysis of legal materials uses qualitative analysis.The results of this research show that the validity of the sale and purchase agreement for fuel oil between the gas station and the retailer is invalid if the retailer is not a business entity and has a permit from the Investment and One-Stop Integrated Services Service because one of the valid conditions for the sale and purchase agreement is an analogous skill requirement. as the authorized party to carry out the sale and purchase of retail fuel oil, this results in an invalid sale and purchase in the eyes of the law because it does not fulfill all the legal requirements for a sale and purchase agreement in Article 1320 of the Civil Code. And the legal consequences resulting from buying and selling retail fuel oil for business actors who do not meet the requirements are administrative sanctions such as revocation of business permits and also criminal sanctions as regulated in Article 55 of Law Number 22 of 2001 concerning Oil and Natural Gas.